Colonial rosary : the Spanish and Indian missions of California - Lake, Alison (Swallow Press/Ohio University Press, 2006)
California would be a different place today without the imprint of Spanish culture and the legacy of Indian civilization. The colonial Spanish missions that dot the coast and foothills between Sonoma and San Diego are relics of a past that transformed California's landscape and its people. In a spare and accessible style, Colonial Rosary looks at the complexity of California's Indian civilization and the social effects of missionary control. While oppressive institutions lasted in California for almost eighty years under the tight reins of royal Spain, the Catholic Church, and the government.